2019
DOI: 10.4269/ajtmh.19-0375
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of Premature and Potentially Preventable Death among Patients Surviving Melioidosis in Tropical Australia

Abstract: Although the in-hospital mortality of Australian patients with melioidosis continues to decline, the ensuing clinical course of survivors is poorly described. Between January 1, 1998, and January 31, 2019, 228 patients in Cairns, tropical Australia, survived their hospitalization with melioidosis; however, 52 (23%) subsequently died. Death occurred at a median of 3.8 years after discharge, with patients dying at a mean age of 59 years. Only 1/27 (4%) without predisposing conditions for melioidosis died during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…As the case-fatality rate from melioidosis declines in Australia, there is a growing focus on the diagnosis of the comorbidities that predispose patients to the infection, which are also associated with subsequent premature, and frequently preventable, death. Indeed, identification of these conditions and optimisation of their subsequent management is now part of routine clinical care of patients diagnosed with melioidosis in Australia [ 2 , 3 ]. Renal impairment will be biochemically apparent, but patients should be screened for diabetes and asked specifically about hazardous alcohol consumption, and symptoms consistent with chronic lung disease and immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the case-fatality rate from melioidosis declines in Australia, there is a growing focus on the diagnosis of the comorbidities that predispose patients to the infection, which are also associated with subsequent premature, and frequently preventable, death. Indeed, identification of these conditions and optimisation of their subsequent management is now part of routine clinical care of patients diagnosed with melioidosis in Australia [ 2 , 3 ]. Renal impairment will be biochemically apparent, but patients should be screened for diabetes and asked specifically about hazardous alcohol consumption, and symptoms consistent with chronic lung disease and immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying these comorbidities is essential as they are closely linked to long term outcomes. While the case-fatality rate from melioidosis is now <10% in Australia, the five-year mortality of patients with predisposing conditions who survive their melioidosis is up to 23%, higher than that of many cancers [ 2 , 3 ]. Identifying and optimising the subsequent management of these comorbidities is likely to improve patients’ long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Melioidosis is a disease complex attributed to a multi-competent Gram-negative bacillus, B. pseudomallei. High rates of mortality in acute melioidosis survivors remain an unresolved problem 33…”
Section: Discussionmentioning
confidence: 99%
“…One Australian cohort found that 23% of survivors subsequently died at a median of 3.8 years after hospital discharge. 140 Death during follow-up was more likely in patients with chronic lung disease (odds ratio: 4.05). 140 Even survivors of sepsis from western countries have been shown to have a mortality up to 40% within the first year, 141 emphasizing the need for a more holistic approach to management beyond the acutely infectious period.…”
Section: Discussionmentioning
confidence: 99%